Study of the Behavior of Water Droplets Under the Influence of a Uniform Electric Field on Conventional Polyethylene and on Crosslinked Polyethylene (XLPE) with MgO Nanoparticles Samples - Charalambous, C.; Danikas, M.; Yin, Y.; Vordos, N.; Nolan, J. W.; Mitropoulos, A. (Engineering, Technology & Applied Science Research, 2017)
It is well known that polyethylene (PE) and cross-linked polyethylene (XLPE) are suitable insulating materials for underground cables. Samples of PE and of XLPE with MgO nanoparticles were investigated regarding their flashover behaviour with a uniform electric field and water droplets of various conductivities. In the present paper, the effect of the mounting arrangement of the water drops on the value of the flashover voltage and the effect of the volume of dripping water on the flashover voltage were also studied. Surface damages were analyzed using Scanning Electron Microscopy (SEM) studies and the study of the nano-structure of the samples was studied using the SAXS system.